Insights on the rapid adoption of Pusa 1121 basmati variety in North India - Joshi, Kuhu; Joshi, Pramod Kumar; Khan, Md. Tajuddin; Kishore, Avinash (International Food Policy Research Institute, 2018)
In this paper we apply duration analysis to study the factors driving the speed of adoption of a popular Basmati rice variety called Pusa 1121. We use data from a primary survey on variety adoption and crop economics conducted in 2017. The sample comprises of 1305 Basmati growing farmers from the north Indian states of Haryana and Punjab. Pusa 1121 was adopted rapidly by 60% farmers between 5 and 10 years from its release in 2005. Results from the duration analysis highlight the key role of superior quality traits of Pusa 1121 and assured market demand. Access to varietal information from extension agents also shortened farmers’ time to adoption. Moreover, we show that early adopters of Pusa 1121 positively influenced other farmers’ speed of adoption within their village network.